2009
DOI: 10.1371/journal.pone.0006469
|View full text |Cite
|
Sign up to set email alerts
|

Does the Clock Make the Poison? Circadian Variation in Response to Pesticides

Abstract: BackgroundCircadian clocks govern daily physiological and molecular rhythms, and putative rhythms in expression of xenobiotic metabolizing (XM) genes have been described in both insects and mammals. Such rhythms could have important consequences for outcomes of chemical exposures at different times of day. To determine whether reported XM gene expression rhythms result in functional rhythms, we examined daily profiles of enzyme activity and dose responses to the pesticides propoxur, deltamethrin, fipronil, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
66
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 45 publications
(65 reference statements)
7
66
1
Order By: Relevance
“…123,124) There are also data showing coordinate control of some esterase, P450 and GST genes mediated by circadian clock genes, with correlated effects on xenobiotic (including permethrin) detoxification. [124][125][126] It is clearly unlikely that circadian clock genes are directly involved in the resistance phenotypes we have reviewed. However these and the microarray data demonstrate that the expression of at least some genes with primary detoxification functions are embedded in larger regulatory networks.…”
Section: Discussionmentioning
confidence: 99%
“…123,124) There are also data showing coordinate control of some esterase, P450 and GST genes mediated by circadian clock genes, with correlated effects on xenobiotic (including permethrin) detoxification. [124][125][126] It is clearly unlikely that circadian clock genes are directly involved in the resistance phenotypes we have reviewed. However these and the microarray data demonstrate that the expression of at least some genes with primary detoxification functions are embedded in larger regulatory networks.…”
Section: Discussionmentioning
confidence: 99%
“…gambiae likely translates into rhythmic patterns of time-of-day susceptibility to insecticide, as found in numerous insects including the mosquito Ae. aegypti (63,64). Interestingly, the metabolic detoxifying genes we identified do not cluster uniformly in time of peak expression.…”
mentioning
confidence: 82%
“…Ace codes for an acetylcholinesterase associated with pesticide resistance (Menozzi et al 2004), which was previously identified as a differentiated CNV between these populations (Turner et al 2008). Interestingly, Ace expression has been shown to vary over the circadian cycle (Hooven et al 2009), and acetylcholinesterase levels are highly correlated with pesticide resistance (Charpentier and Fournier 2001).…”
Section: And Eip93fmentioning
confidence: 98%